What works to reduce sedentary behavior in the office, and could these intervention components transfer to the home working environment?: A rapid review and transferability appraisal - Morton, Sarah; Fitzsimons, Claire; Jepson, Ruth; Saunders, David H.; Sivaramakrishnan, Divya; Niven, Ailsa (Frontiers in Sports and Active Living, 2022)
Background Working patterns have changed dramatically due to COVID-19, with many workers now spending at least a portion of their working week at home. The office environment was already associated with high levels of sedentary behavior, and there is emerging evidence that working at home further elevates these levels. The aim of this rapid review (PROSPERO CRD42021278539) was to build on existing evidence to identify what works to reduce sedentary behavior in an office environment, and consider whether these could be transferable to support those working at home. Methods The results of a systematic search of databases CENTRAL, MEDLINE, Embase, PsycInfo, CINHAL, and SportDiscus from 10 August 2017 to 6 September 2021 were added to the references included in a 2018 Cochrane review of office based sedentary interventions. These references were screened and controlled peer-reviewed English language studies demonstrating a beneficial direction of effect for office-based interventions on sedentary behavior outcomes in healthy adults were included. For each study, two of five authors screened the title and abstract, the full-texts, undertook data extraction, and assessed risk of bias on the included studies. Informed by the Behavior Change Wheel, the most commonly used intervention functions and behavior change techniques were identified from the extracted data. Finally, a sample of common intervention strategies were evaluated by the researchers and stakeholders for potential transferability to the working at home environment. Results Twenty-two studies including 29 interventions showing a beneficial direction of effect on sedentary outcomes were included. The most commonly used intervention functions were training (n = 21), environmental restructuring (n = 21), education (n = 15), and enablement (n = 15). Within these the commonly used behavior change techniques were instructions on how to perform the behavior (n = 21), adding objects to the environment (n = 20), and restructuring the physical environment (n = 19). Those strategies with the most promise for transferring to the home environment included education materials, use of role models, incentives, and prompts. Conclusions This review has characterized interventions that show a beneficial direction of effect to reduce office sedentary behavior, and identified promising strategies to support workers in the home environment as the world adapts to a new working landscape. Systematic Review Registration:https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42021278539, identifier CRD42021278539.